"There's a housing crisis going on in Sydney for Aboriginal people": focus group accounts of housing and perceived associations with health - Melanie J. Andersen; Anna B. Williamson; Peter Fernando; Sally Redman; Frank Vincent (BMC, 2016)
Abstract Background Poor housing is widely cited as an important determinant of the poor health status of Aboriginal Australians, as for indigenous peoples in other wealthy nations with histories of colonisation such as Canada, the United States of America and New Zealand. While the majority of Aboriginal Australians live in urban areas, most research into housing and its relationship with health has been conducted with those living in remote communities. This study explores the views of Aboriginal people living in Western Sydney about their housing circumstances and what relationships, if any, they perceive between housing and health. Methods Four focus groups were conducted with clients and staff of an Aboriginal community-controlled health service in Western Sydney (n = 38). Inductive, thematic analysis was conducted using framework data management methods in NVivo10. Results Five high-level themes were derived: the battle to access housing; secondary homelessness; overcrowding; poor dwelling conditions; and housing as a key determinant of health. Participants associated their challenging housing experiences with poor physical health and poor social and emotional wellbeing. Housing issues were said to affect people differently across the life course; participants expressed particular concern that poor housing was harming the health and developmental trajectories of many urban Aboriginal children. Conclusions Housing was perceived as a pivotal determinant of health and wellbeing that either facilitates or hinders prospects for full and healthy lives. Many of the specific health concerns participants attributed to poor housing echo existing epidemiological research findings. These findings suggest that housing may be a key intervention point for improving the health of urban Aboriginal Australians.